Kuźnia z Porszewic, powiat Pabianice, województwo łódzkie jako dokument architektury i rzemiosła wiejskiego - Czepas, Piotr (Zbiór Wiadomości do Antropologii Muzealnej, 2018)
This article is a presentation of the history of a smithy, located in the village of Porszewice, in Pabianicki County, Łódzkie Voivodeship. The forge was established at the beginning of the 20th century and worked almost uninterruptedly until 2012 when it was purchased by the Museum of Archaeology and Ethnography in Łódź. Throughout its existence, the forge was connected with the activities of the Górniak family, who had a tradition of blacksmithing for over a century. Currently, the forge is open to the public at the Łęczycka Zagroda Chłopska open-air museum in Kwiatkówek, which is part of the Museum of Archaeology and Ethnography in Łódź.